Kelayakan Masker Mentimun Dan Tepung Beras Untuk Mencegah Kulit Berjerawat - Zahra Zegita; Rahmiati (Jurnal Tata Rias, 2024)
Cucumber  is  a  type  of  vegetable  that  can  be  used  as  a  basic  ingredient  for  making  masks. Cucumbers can be used as a cool, refreshing ingredient, a cleanser, a moisturizer, and for acne-prone skin care.  To  prevent  acne-prone  skin,  you  can  use  a  mask  made  from  natural ingredients, namely, cucumber mixed with rice flour. Cucumbers contain many vitamins, such as vitamin A and vitamin C, while rice flour contains gemma oryznol, which is effective in forming melanin pigment, acting as an antioxidant and protecting against ultraviolet rays. This study aims to test the suitability of a cucumber and rice flour mask for preventing acne.  The research method used is a quantitative experiment. By carrying out organoleptic tests and hedonic tests. The data analysis technique in this research uses percentages. Based on the research results, the panelists' preferences indicated that a mask made from cucumber and rice flour was suitable for preventing acne-prone skin.